THE EFFECT OF SMALL GROUP DISCUSSION EDUCATION METHOD ON KNOWLEDGE OF SEXUAL VIOLENCE PREVENTION AMONG ADOLESCENT - Arif, Rifda Nur Achriyana; Islamiyah, Tsuwaibatul; Saadah Ayu Lestari, Hayatus; Olsi Rahmi, Yuza; Muthmainnah (Jurnal Penelitian Keperawatan Kontemporer, 2025)
Background: Sexual violence against teenage girls, especially those living in orphanages, has become a serious issue that impacts physical, psychological, and social aspects. The lack of education and supervision makes this group vulnerable to sexual violence. Aim: This study aims to analyze the impact of audiovisual lecture education methods combined with Small Group Discussion (SGD) on the improvement of knowledge among adolescent girls about the prevention of sexual violence. Method: The research used a quasi-experimental design with one group pre-test and post-test involving a total of 32 female adolescent respondents at the Muhammadiyah Orphanage in Banjar Regency. The intervention was conducted over two days through the delivery of educational material using audiovisual lectures and group discussions. Data analysis used the Wilcoxon Signed-Rank test. Results: The results showed a significant increase in knowledge scores after the intervention, with a p-value of 0.000 (p < 0.05). Conclusion: The educational method combining audiovisual lectures and small group discussions has proven effective in increasing the knowledge of adolescent girls in preventing sexual violence. This study recommends the implementation of this method as a preventive educational program in orphanage environments.